Plasmonic Bi promotes the construction of Z-scheme heterojunction for efficient oxygen molecule activation. (September 2022) - Chen, Yongbo; Zhou, Yi; Zhang, Jin; Li, Jiaxin; Yao, Tiantian; Chen, Anna; Xiang, Minghui; Li, Qionghua; Chen, Zhiyue; Zhou, Yinghong
Abstract: Reactive oxygen species (ROS) are essential to photocatalytic degradation of antibiotics in water. In this work, we prepared Ag3 PO4 /Bi@Bi4 Ti3 O12 by simple in-situ reduction method and precipitation method, which improves the ability to capture visible light and increases the activity of photoinduced molecular oxygen activation, resulting in reactive oxygen species (ROS) such as superoxide radicals (O2 − ), hydroxyl radicals (OH), and H2 O2 . The excellent TC degradation efficiency derive from the SPR effect of the metal Bi on the surface enhances the light absorption intensity, and development of a Z-scheme heterojunction between Ag3 PO4 and Bi4 Ti3 O12 promotes the activation of molecular oxygen. A possible photodegradation mechanism of the as-prepared photocatalyst was proposed. This work provides an insight perspective to the synthesis photocatalysts with molecular oxygen activation for environmental remediation. Graphical abstract: Image 1 Highlights: A novel ternary Z-scheme heterojunction of Ag3 PO4 /Bi@Bi4 Ti3 O12 was fabricated. SPR effect and Z-scheme heterojunction enhance molecular activation. Step-scheme charge separation mechanism in Ag3 PO4 /Bi@Bi4 Ti3 O12 was verified. The Ag3 PO4 /Bi@Bi4 Ti3 O12 exhibit excellent photocatalytic efficiency.